2016
DOI: 10.1016/j.jacc.2016.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for Premature Senescence of Myofibroblasts in Myocardial Fibrosis

Abstract: Our data establish premature senescence of myofibroblasts as an essential antifibrotic mechanism and potential therapeutic target in myocardial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
168
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(182 citation statements)
references
References 41 publications
13
168
1
Order By: Relevance
“…In the heart, ischemia/reperfusion induces CCN1 expression in cardiomyocytes, serving as an autocrine function to mediate the cardioprotective effects 15. Another study demonstrated that cardiac‐specific overexpression of CCN1 possessed antifibrosis effects in cardiac fibrosis, suggesting that CCN1 linked a cardiomyocyte–fibroblast interaction 10. Considering that pathological fibrosis is vital in AMI‐induced heart malfunction, we speculate that cardiomyocyte‐derived CCN1 may protect the heart by preventing pathological fibrosis.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In the heart, ischemia/reperfusion induces CCN1 expression in cardiomyocytes, serving as an autocrine function to mediate the cardioprotective effects 15. Another study demonstrated that cardiac‐specific overexpression of CCN1 possessed antifibrosis effects in cardiac fibrosis, suggesting that CCN1 linked a cardiomyocyte–fibroblast interaction 10. Considering that pathological fibrosis is vital in AMI‐induced heart malfunction, we speculate that cardiomyocyte‐derived CCN1 may protect the heart by preventing pathological fibrosis.…”
Section: Introductionmentioning
confidence: 86%
“…It was reported that myofibroblast senescence possessed antifibrosis effects in cardiac fibrosis 10. Moreover, cardiomyocyte senescence is implicated in the myocardial damage caused by doxorubicin and obesity 16, 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic inactivation of senescence effectors accelerates the development and complexity of atherosclerotic plaques (Merched and Chan, 2004; Guevara et al, 1999) and increases fibrosis following transverse aortic constriction (Meyer et al, 2016). These findings mirror conclusions derived from studies of senescence effector inactivation in liver, which support restrictive function in fibrotic pathogenesis (Krizhanovsky et al, 2008).…”
Section: Cellular Senescence: Aging Mechanism Activated By Nutrienmentioning
confidence: 99%
“…Comparable phenomena have been observed in cardiac tissue, wherein, accumulation of senescence markers is associated with vascular endothelial and cardiac impairments, and clearance of senescent cells improves cardiovascular dysfunction (Roos et al, 2016). Antithetically, defective senescence effector function intensifies cardiovascular disease (Merched and Chan, 2004; Guevara et al, 1999; Meyer et al, 2016). Since p16 INK4a , p53, and p21 exert well-known pleiotropic functions, which convey both anti-proliferative and pro-aging effects, context is essential for interpreting results.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%